2021
DOI: 10.31616/asj.2020.0072
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Epidural Ropivacaine with or without Dexmedetomidine on Postoperative Analgesia and Patient Satisfaction after Thoraco-Lumbar Spine Instrumentation: A Randomized, Comparative, and Double-Blind Study

Abstract: This was a prospective, randomized, and double-blind study. Purpose: Thoraco-lumbar spine surgery is associated with severe postoperative pain and can cause chronic pain. We aimed to compare the impact of epidural ropivacaine with and without dexmedetomidine on postoperative analgesia after thoracolumbar spine instrumentation wherein an epidural catheter was placed by the surgeon intraoperatively. Overview of Literature: Very few studies have reported the use of epidural dexmedetomidine in spine surgeries. Whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Pain-relieving effect of epidural dexmedetomidine as a sole adjuvant has been searched in different surgeries: orthopedic, abdominal and spine surgeries [17][18][19][20]. A study done in our university hospitals in 2019 by Alansary et al [21] showed that addition of 50 µg dexmedetomidine to epidural bupivacaine provided better postoperative pain control than addition of 50 µg fentanyl in lumbar disc operations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pain-relieving effect of epidural dexmedetomidine as a sole adjuvant has been searched in different surgeries: orthopedic, abdominal and spine surgeries [17][18][19][20]. A study done in our university hospitals in 2019 by Alansary et al [21] showed that addition of 50 µg dexmedetomidine to epidural bupivacaine provided better postoperative pain control than addition of 50 µg fentanyl in lumbar disc operations.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned, studies demonstrated that dexamethasone and dexmedetomidine can prolong duration of epidural analgesia after spine surgeries when used as sole agents [16,20]. The mechanism by which each drug increase the duration of local anesthetics is not completely known but different actions of these drugs have been documented.…”
Section: Discussionmentioning
confidence: 99%
“…Epidural steroid injection is indicated for acute radiating pain and nervous claudication that are interfering with daily life despite pain relievers and rest, which are expected to improve symptoms [45]. In addition, research on the use of ropivacaine and dexmedetomidine as well as epidural neuroplasty in conjunction with thoracolumbar surgery has been recently published [46,47]. Epidural neuroplasty is employed to alleviate back discomfort and/or radiating pain caused by mechanical compression of the intravertebral nerve structures or neuroinflammation.…”
Section: Epidural Steroid Injection and Othersmentioning
confidence: 99%
“…[ 1 ] Inadequate postoperative pain relief may lead to increased morbidity and mortality and may delay recovery. [ 2 ] Nonsteroidal anti-inflammatory drugs or opioids are commonly used for postoperative pain in spine surgeries but are associated with side effects and wide variations in their clinical effects. Epidural analgesia is an effective and safe method in spine surgeries to avoids unwanted side effects.…”
Section: Introductionmentioning
confidence: 99%
“…[ 9 ] Although the use of dexmedetomidine has been extensively studied for postoperative epidural analgesia with epidural catheter in situ. [ 2 10 ] Still, there have been no studies on epidural administered gelfoam soaked dexmedetomidine to enhance postoperative analgesia. Thus, this study was to evaluate the effectiveness of drugs such as dexmedetomidine or bupivacaine in the form of soaked gelfoam placed over epidural space for postoperative analgesia.…”
Section: Introductionmentioning
confidence: 99%